L-T4 Therapy in the Presence of Pharmacological Interferents - Benvenga, Salvatore (Frontiers in Endocrinology, 2020)
Pharmacological interference on L-thyroxine (L-T4) therapy can be exerted at several levels, namely from the hypothalamus/pituitary through the intestine, where the absorption of exogenous L-T4 takes place. A number of medications interfere with L-T4 therapy, some of them also being the cause of hypothyroidism. The clinician should be aware that some medications simply affect thyroid function tests with no need of modifying the dose of L-T4 that the patient was taking prior to their prescription. Usually, the topic of pharmacological interference on L-T4 therapy addresses the patient with primary hypothyroidism, in whom periodic measurement of serum thyrotropin (TSH) is the biochemical target. However, this minireview also addresses the patient with central hypothyroidism, in whom the biochemical target is serum free thyroxine (FT4). This minireview also addresses two additional topics. One is the costs associated with frequent monitoring of the biochemical target when L-T4 is taken simultaneously with the interfering drug. The second topic is the issue of metabolic/cardiovascular complications associated with undertreated hypothyroidism.